Karakterisasi Edible Film dari Pati Propagul Mangrove Lindur (Bruguiera gymnorrhiza) dengan Penambahan Carboxymethyl Cellulose (Cmc) sebagai Pemlastis [Characterization of Edible Film From Propagules Mangrove Lindur (Bruguiera Gymnorrhiza) Starch with Addition of Carboxymethyl Cellulose (Cmc) as Plasticizer] - Moch Amin Alamsjah; Sudarno Sudarno; Azka Prima Nurindra (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract The using of synthetic packaging generally has a problem for healthy and nature. This plastic rubbish can't degredable by nature and soil. Necessary alternative packaging technology which safe and degredable that is edible film. Use of single material in edible film as starch have some shortage, that is brittle and rigid. Therefore, it is necessary to add material as plasticizer. Plasticizer that use in this study is Carboxymethyl Cellulose. This purpose of this study is to know the effect addition of carboxymethyl cellulose on characterization edible film from propagules mangorve B.gymnorrhiza. The method of this study is experimental with Completely Randomized Design. The treatment is concentration addition of CMC, that is A (0%), B (0,2%), C (0,4%), D (0,6%), E (0,8%), F (1%) and G (1,2%), with four repeatations. Parameters measured were thcikness, water vapor transmission rate, tensile strength and elongation at break. Data analysis using Analysis of Varioan (ANOVA) and if there is difference significant on the result, further with Duncan's Multiple Range Test. The result of this study show that addition of CMC have different very significant (p<0,01) on thickness, water vapor transmission rate, tensile strength and elongation at break. The best treatment in this study is treatment G (addition CMC concentration 1,2%) with scoring method which basicaly on JIS (Japanesse Industrial Standard)